Hikmah Sedekah dalam al-Qur’an dan Hadis - Teguh Saputra (UIN Sunan Gunung Djati Bandung, 2022)
This research uses qualitative research through literature study with an interpretive approach, namely the interpretation of al-Azhar by Buya Hamka and applies content analysis as a tool to explore the collected data so that it can lead to conclusions. The results and discussion of this study explain that alms means giving something in the form of material or non-material to someone with the sole aim of getting Allah's blessing without wanting anything in return from someone who is given and behind this alms there are some lessons that can be felt in The world, such as material and non-material things that are lawful, continue to be given in charity sincerely, will be rewarded multiplied by Allah swt with the arrival of various sustenance to those who give charity and the wisdom of alms can also be felt in the hereafter, such as giving charity will get shade on the Day of Judgment later then giving charity can keep away from hell fire. In addition, giving charity can also form a good character, such as helping and caring for society, and by giving charity can also create prosperity and peace. This study concludes that the wisdom of alms in the Qur'an and Hadith can be felt in this world and in the hereafter. This study recommends that research be conducted on errors in giving alms using the maudhui method.